2019
DOI: 10.1016/j.ejca.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Pathologist-level classification of histopathological melanoma images with deep neural networks

Abstract: Background: The diagnosis of most cancers is made by a board-certified pathologist based on a tissue biopsy under the microscope. Recent research reveals a high discordance between individual pathologists. For melanoma, the literature reports 25e26% of discordance for classifying a benign nevus versus malignant melanoma. Deep learning was successfully implemented to enhance the precision of lung and breast cancer diagnoses. The aim of this study is to illustrate the potential of deep learning to assist human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(106 citation statements)
references
References 18 publications
1
91
0
8
Order By: Relevance
“…Géraud et al [74] found that 15% of the images used in the trial had no recognizable melanocytic lesion whatsoever, which indicates that these images only contained perilesional normal skin tissue. Hekler et al [77] also released a similar study a few months earlier with the same methods and model, claiming that their models achieved pathologist-level classification of histopathological melanoma images, but this study still has the same pitfalls.…”
Section: Dermatopathologymentioning
confidence: 99%
“…Géraud et al [74] found that 15% of the images used in the trial had no recognizable melanocytic lesion whatsoever, which indicates that these images only contained perilesional normal skin tissue. Hekler et al [77] also released a similar study a few months earlier with the same methods and model, claiming that their models achieved pathologist-level classification of histopathological melanoma images, but this study still has the same pitfalls.…”
Section: Dermatopathologymentioning
confidence: 99%
“…Eine ebenfalls häufige Fragestellung ist die Unterscheidung zwischen benignen und malignen melanozytären Tumoren. Hekler et al trainierten ein Deep-Learning-System auf die Unterscheidung zwischen benignen Nävi und malignen Melanomen [11]. Der Algorithmus zeigte in 19 % der Fälle eine Abweichung zum Standarduntersucher im Vergleich zu bis zu 25 % Abweichungen zwischen 2 verschiedenen Untersuchern [11].…”
Section: Dermatopathologieunclassified
“…To classify skin lessons, She et al [28] use several features like diameter, color, border, and asymmetry. To attain skin lesion segmentation, several pre-processing methods such as artificial removal, color transformation, lesion localization, contrast enhancement can be employed [29].…”
Section: Related Workmentioning
confidence: 99%